2012
DOI: 10.2355/tetsutohagane.98.358
|View full text |Cite
|
Sign up to set email alerts
|

Machinability Improvement and Its Mechanism in SUS304 Austenitic Stainless Steel by h-BN Addition

Abstract: In order to improve the machinability of Type 304 austenitic stainless steels, 0.016 mass % boron and 0.2 mass % nitrogen were added, and hexagonal boron nitride (h-BN) particles (1~5 μm diameter) were precipitated. During turning with cemented carbide insert, cutting force and tool wear were reduced by h-BN precipitation, especially at higher cutting speed of more than 40 m/min. The reduction of cutting force seems to be due to the internal lubrication effect of h-BN in chip shear region and deformation flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…During solidification, sulfur combines with manganese to form manganese sulfide (MnS) non-metallic inclusions. Manganese sulfides play a vital role in improving machinability [4,8,9]. When machining, MnS acts as a lubricant, reducing friction and extending tool life while yielding a superior surface finish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During solidification, sulfur combines with manganese to form manganese sulfide (MnS) non-metallic inclusions. Manganese sulfides play a vital role in improving machinability [4,8,9]. When machining, MnS acts as a lubricant, reducing friction and extending tool life while yielding a superior surface finish.…”
Section: Introductionmentioning
confidence: 99%
“…The use of boron nitride (BN) also demonstrated enhanced machinability in austenitic stainless steels [9] and heat-treatable steels [10,11]. Chen et al showed the potential benefits of using both manganese sulfides (MnS) and boron nitride (BN) simultaneously to improve machinability [12].…”
Section: Introductionmentioning
confidence: 99%
“…Stainless steels are widely used to manufacture mechanical components because of its outstanding mechanical properties, corrosion resistance and good weldability [1]. It contains chromium which prevents corrosion of the steel.…”
Section: Introductionmentioning
confidence: 99%